Impact of renal function in patients with multi-vessel coronary disease on long-term mortality following coronary artery bypass grafting compared with percutaneous coronary intervention - Sugumar, H.; Lancefield, T.; Andrianopoulos, N.; Duffy, S.; Ajani, A.; Freeman, M.; Buxton, B.; Brennan, A.; Yan, B.; Dinh, D.; Smith, J.; Charter, K.; et al. (2014)
Background Comorbidities, such as diabetes, affect revascularization strategy for coronary disease. We sought to determine if the degree of renal impairment affected long-term mortality after percutaneous coronary intervention (PCI) compared to coronary artery bypass grafting (CABG) in patients with multi-vessel coronary disease (MVD). Methods and results 8970 patients with MVD undergoing revascularization between 2004 and 2008, in two multi-center parallel PCI and CABG Australian registries were assigned to three groups based on their estimated glomerular filtration rate (eGFR) = 60 mL/min/1.73 m2 (n = 1678:839), 30-59 mL/min/1.73 m2 (n = 452:226) and < 30 mL/min/1.73 m2 (n = 74:37). We used 2:1 propensity matching to compare 3306 patients undergoing primary CABG versus PCI. Shock, myocardial infarction (MI) < 24 h, previous CABG, valve surgery or PCI were exclusions. Long-term mortality (mean 3.1 years) was compared with Cox-proportional hazard-adjusted modeling. Observed long-term mortality rates (CABG vs. PCI) were 4.5% vs. 4.3% p = 0.84, 12.8% vs. 17.3% p = 0.12, and 23.0% vs. 40.5% p = 0.05 in the three strata, respectively. In patients with eGFR = 60 mL/min/1.73 m2, long-term mortality between PCI and CABG (HR 0.99, 95% CI 0.65-1.49, p = 0.95) was similar. However, amongst patients with eGFR 30-59 mL/min/1.73 m2, there was a significant mortality hazard with PCI (HR 2.00, 95% CI 1.32-3.04, p = 0.001). In patients with eGFR < 30 mL/min/1.73 m2, there was a trend for hazard with PCI (HR 1.66, 95% CI 0.80-3.46, p = 0.17). Conclusion Long-term mortality in MVD patients with preserved renal function was very low and similar between PCI and CABG. However there was a long-term mortality hazard associated with PCI amongst patients with moderate renal impairment. © 2014 Elsevier Ireland Ltd.